MOTIVATION FACTORS OF ENGINEERS IN PRIVATE SECTOR CONSTRUCTION INDUSTRY - Sugathadasa, Ranil; De Silva, Mavin Lakshitha; Thibbotuwawa, Amila; Bandara, K.A.C.P. (Journal of Applied Engineering Science, 2021)
Human resource in today’s world is recognized as a strategic asset which drives organizations to superior in the industrial competition. With the effective identification of employee attributes, all the determinants of productivity can be obtained. This research assesses engineers’ motivation factors in the construction industry’s private sector and further examined their response to various attributes, including age and gender. A structured and self-administrated systematic qualitative approach was utilized to collect data from 120 engineers. Twenty-six motivational factors were grouped according to Maslow’s need theory, and the paper presents a comprehensive analysis based on the relative importance and response percentages of the identified factors. The most influential need level among them was statically determined as the esteem needs to be followed by basic needs, belonging needs, safety needs, and self-actualization needs. Out of the twenty-six factors, good work discipline is the most influential motivational factor for female engineers, whereas company name and stability have become the most important factor for male engineers. A variation of those factors’ relative importance is also determined for various age groups. These results would help senior management to formulate effective policies to improve employee retention in the construction industry.